Induced Inflammatory and Oxidative Markers in Cerebral Microvasculature by Mentally Depressive Stress - Yuequan Zhu; Yazeed Haddad; Ho Jun Yun; Xiaokun Geng; Yuchuan Ding (Hindawi Limited, 2023)
Background. Cerebrovascular disease (CVD) is recognized as the leading cause of permanent disability worldwide. Depressive disorders are associated with increased incidence of CVD. The goal of this study was to establish a chronic restraint stress (CRS) model for mice and examine the effect of stress on cerebrovascular inflammation and oxidative stress responses. Methods. A total of forty 6-week-old male C57BL/6J mice were randomly divided into the CRS and control groups. In the CRS group (n=20), mice were placed in a well-ventilated Plexiglas tube for 6 hours per day for 28 consecutive days. On day 29, open field tests (OFT) and sucrose preference tests (SPT) were performed to assess depressive-like behaviors for the two groups (n=10/group). Macrophage infiltration into the brain tissue upon stress was analyzed by measuring expression of macrophage marker (CD68) with immunofluorescence in both the CRS and control groups (n=10/group). Cerebral microvasculature was isolated from the CRS and controls (n=10/group). mRNA and protein expressions of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), vascular cell adhesion molecule-1 (VCAM-1), and macrophage chemoattractant protein-1 (MCP-1) in the brain vessels were measured by real-time PCR and Western blot (n=10/group). Reactive oxygen species (ROS), hydrogen peroxide (H2O2), and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) activities were quantified by ELISA to study the oxidative profile of the brain vessels (n=10/group). Additionally, mRNA and protein expressions of NOX subunits (gp91phox, p47phox, p67phox, and p22phox) in the cerebrovascular endothelium were analyzed by real-time PCR and Western blot (n=10/group). Results. CRS decreased the total distances (p<0.05) and the time spent in the center zone in OFT (p<0.001) and sucrose preference test ratio in SPT (p<0.01). Positive ratio of CD68+ was increased with CRS in the entire region of the brain (p<0.001), reflecting increased macrophage infiltration. CRS increased the expression of inflammatory factors and oxidative stress in the cerebral microvasculature, including TNF-α (p<0.001), IL-1β (p<0.05), IL-6 (p<0.05), VCAM-1 (p<0.01), MCP-1 (p<0.01), ROS (p<0.001), and H2O2 (p<0.001). NADPH oxidase (NOX) was activated by CRS (p<0.01), and mRNA and protein expressions of NOX subunits (gp91phox, p47phox, p67phox, and p22phox) in brain microvasculature were found to be increased. Conclusions. To our knowledge, this is the first study to demonstrate that CRS induces depressive stress and causes inflammatory and oxidative stress responses in the brain microvasculature.